The influence of language style (formal vs. colloquial) on the effectiveness of charitable appeals. Issue 3 (23rd September 2022) - Pfeiffer, Bruce E.; Sundar, Aparna; Cao, Edita
Abstract: This paper investigates the influence of language style (formal vs. colloquial) on the effectiveness of charitable appeals. Although prior research has found persuasive effects associated with colloquial language style, we propose that the influence of language style is context dependent. Charitable appeals generally address relatively serious topics. Since formal language style is more context congruent in communicating this seriousness, it should be more effective in expressing the emotional arousal or the effort of the communicator, which we expected to result in greater charitable support. Across four studies, we provide important insights on how charitable organizations can better align language style to increase donor support. We find that formal language style (vs. colloquial) results in greater charitable support. We also find evidence for the underlying role of perceptions of emotional arousal, as in indication of effort, in this relationship. Lastly, we find support for a moderator related to one's prior beliefs. Since individuals with high just‐world beliefs are motivated to vary their prosocial behaviors, we find a moderating effect of just‐world beliefs, but only when the belief is high, that is, when individuals seek accountability.